The modern labour market in Poland and the generation. The differences between generations X, Y and Z. - Karolina Martyna Czyczerska; Anna Jadwiga Ławnik; Elżbieta Szlenk-Czyczerska (Rozprawy Społeczne)
Abstract The contemporary labour market in Poland is undergoing constant transformations, which result from demographic changes, mainly related to the process of population ageing. There are currently four generations in the structures of companies and institutions. These generations are more and more often operating in the same teams of employees, which may be a significant challenge for the managers of modern organisations.